Enhanced scavenging of a minor component from mixtures of two immiscible liquids by hollow polymer microgels. Issue 3 (4th January 2022) - Anakhov, Mikhail V.; Gumerov, Rustam A.; Potemkin, Igor I.
Abstract : Hollow soft nanoparticles possess both the high absorption capacity and the ability to change their shape. Abstract : Hollow soft nanoparticles are known to be highly versatile containers with high absorption capacity for various substances. In particular, this feature can be applied in terms of solvent separation on the molecular level. In our work, we systematically studied the absorption of a minor component in an asymmetric mixture of two immiscible liquids (like oil and water) by polymer microgels with an inner cavity by means of mesoscopic computer simulations. Our results revealed the presence of two distinct absorption regimes: localization of the absorbed liquid in the microgel shell or in the cavity. Moreover, it was shown that under certain conditions the microgels attain an anisotropic form after the uptake. At the same time, the presence of the cavity increases the absorption capacity of the microgels and shifts the aggregation threshold to the higher values of concentration of the minor component in comparison to the microgels with a regular (continuous) structure. Our findings can be useful for obtaining anisotropic particles as well as for the design of efficient water purification systems.